Metamaterial unipolar quantum optoelectronics for mid-infrared free-space optics - T. Bonazzi; H. Dely; P. Didier; D. Gacemi; B. Fix; M. Beck; J. Faist; A. Harouri; I. Sagnes; F. Grillot; A. Vasanelli; C. Sirtori (APL Photonics)
Free-space optical communications in the mid-infrared transparency windows (4–5 and 8–14 μm wavelength regions) is emerging as a viable solution for high bitrate data transmission. Unipolar quantum optoelectronics is the technology of choice for data communication in this wavelength region, thanks to the high frequency response of detectors and modulators. In this work, it is demonstrated that the performances of these devices can be substantially enhanced by embedding them into metamaterials. It is also shown that metamaterials have to be engineered differently in detectors than in modulators, as the role of light–matter interaction must be tuned adequately in the two devices. Metamaterial-enhanced performances allow the realization of data transmission with a record rate of 68 Gbit/s, while ensuring robustness and consistency, as it should be for real-world applications. These findings underscore the promising role of metamaterial-enhanced unipolar devices in advancing free-space optical communication systems.